New directions in pharmaceutical amorphous materials and amorphous solid dispersions, a tribute to Professor George Zografi - Proceedings of the June 2016 Land O'Lakes Conference - Ann Newman; Jayne E. Hastedt; Mehran Yazdanian (SpringerOpen, 2017)
Abstract The University of Wisconsin-Madison June Land O'Lakes Conference on Research and Development is held every year and is recognized worldwide as a premier teaching conference for pharmaceutical scientists. The conference held in June 2016 was a tribute to the ground-breaking work of Emeritus Professor and Dean George Zografi of School of Pharmacy, University of Wisconsin-Madison. This paper provides a summary of the wide range of topics in the areas of amorphous drugs, amorphous solid dispersions, mesophases, mesoporous supports, cocrystals, and related themes that were covered at this conference.